Predictors of Mother-Child Bonding - Mina Galeshi; Mojgan Mirghafourvand; Fariba Alizadeh-Sharajabad; Favziye Sanaati (Tehran University of Medical Sciences, 2016)
Background & Aim: Mother-Child bonding is an emotional aspect of relationship between mother and baby that affects childrenchr('39')s psychological development. This study was performed to determine the predictors of mother-child bonding. Methods & Materials: This cross-sectional study was performed on 270 mothers 8 to 10 weeks postpartum referred to eighteen health centers of Tabriz, 2014-2015. Data were collected using the obstetric and socio-demographic characteristics questionnaire, the Postpartum Bonding Questionnaire, the Edinburgh Postnatal Depression Scale and the Spielberger State-Trait Anxiety Inventory. The statistical tests including Pearson correlation, Independent t, one-way ANOVA and multivariate linear regression were used for data analysis through SPSS v.21. The significance level was considered as P<0.05. Results: The mean (SD) of mother-child bonding score was 46.2±8.4, with achievable scores range from 0 to 125. 85.2% of mothers had a mother-child bonding disorder. The most frequent disorder pertained to the dimension of impaired mother-child bonding and the least frequent disorder was anxiety about child care. Variables of depression, state anxiety and unwanted pregnancy were among the predictors of mother-child bonding. Conclusion: The study shows that anxiety, depression, and unwanted pregnancy are the determinants affecting mother-child bonding. Thus, the screening of mothers for the early identification and treatment of anxiety and depression, and also the reduction of unwanted pregnancy rate using purposeful family planning counseling can improve the mother-child bonding, resulting in improved childrenchr('39')s growth and development.